Community development through food tourism: exploring the utilization of local food as community development at rural destination in Malaysia - Abdul Raji, Mohd Nazri; Abdul Karim, Muhammad Shahrim; Arshad, Mohd Mursyid; Che Ishak, Farah Adibah (Human Resource Management Academic Research Society, 2018)
Many regions have recognized local foods as icons of their countries and act as one of important attributes of developing a destination. The availability of local foods provides travellers and local consumers with positive memorable experiences. Tourism destinations are competing to promote food tourism which is an emerging segment in the tourism industry. In this regard, rural destination is no exception. From the tourism perspective, rural destinations mainly focused on nature, historical sites, and practices of host community, landscape and cultural heritage as well as local food products. There are many benefits highlighting local food product as tourist attraction at rural destination. The importance of local foods at rural destinations to develop connection to the place, create diverse tourists’ experience, and provide financial support to the local community well-being cannot be underestimated. Furthermore, in the context of rural area local food is considered as a symbol and practices of traditional culture heritage of the people. For instance, by participating in local food activities, tourists will have the opportunity to experience different local cultures and practices. Key stakeholders and relevant authorities of rural destinations must aware the advantage of local foods in promoting their destinations and the contribution to the local economy. By integrating local foods in rural destinations will help to strengthen destinations’ sustainability competitiveness. However, without support from the local community, it will be impossible to promote the destinations. Technically, local community’s participant is important to promote any tourism products particularly in rural destinations, as local communities can reflect the surroundings and how they can work together to benefit the community and visitors. Therefore, this conceptual paper explores the viability of the community of a rural destination using local foods as determinants towards rural tourism destination development.